EDUCATION AND SUPPORT INTERVENTION ON BREASTFEEDING TECHNIQUES IN POSTPARTUM MOTHERS: A CASE STUDY - Nurliawati, Enok (Jurnal JKFT, 2023)
Background: Breastfeeding is inherent to a woman, just as pregnancy and childbirth. However, not all women succeed in breastfeeding their infants. One of the factors influencing successful breastfeeding is the correct breastfeeding technique. Method: This research employs a descriptive-analytical design with a case study approach to explore nursing care for postpartum mothers. The focus is on education and support interventions for breastfeeding techniques. The study involves one subject receiving combined care. Data collection is conducted through interviews, physical examinations, and observations, using a nursing care format for postpartum mothers. Results: Based on the assessment, the established nursing diagnoses include postpartum discomfort related to  perineal trauma, knowledge deficit: breastfeeding technique related to lack of information, maternal infection risk related to skin integrity damage, and infant infection risk related to tissue integrity damage (umbilical cord). Interventions primarily address knowledge deficit: breastfeeding technique related to lack of information. After 2 days of education and support interventions, the knowledge level regarding breastfeeding techniques has improved. Conclusion: Education and support interventions for breastfeeding techniques can be implemented for postpartum mothers diagnosed with ineffective breastfeeding or knowledge deficit in breastfeeding techniques. Keywords: Education, support, breastfeeding techniques, postpartum.